Are European Union sanctions "targeted"?. Issue 3 (2nd July 2016) - Portela, Clara
Abstract: The emergence of targeted sanctions in the mid-1990s was due to the humanitarian impact of embargoes, which were deemed unacceptable and compelled senders to shift to measures designed to affect only wrongdoers. Twenty years on, the present paper considers the extent to which autonomous sanctions are designed to affect those individuals and elites responsible for the behaviour the EU aims to condemn. How faithful has the EU remained to this concept in its sanctions policy? The enquiry scrutinizes diverse practices in three established sanctions strands of the EU, development aid suspensions, Common Foreign and Security Policy (CFSP) sanctions and Generalised Scheme of Preferences (GSP) withdrawals. It shows that it has been more faithfully implemented in some strands of EU sanctions than in others. Specifically in the flagship CFSP sanctions practice, the due process motivated court challenges of its blacklists have led the EU to modify selection criteria in a way that renders them potentially less targeted.